Microbleed prevalence and burden in anticoagulant‐associated intracerebral bleed. Issue 8 (10th July 2019) - Lioutas, Vasileios‐Arsenios; Goyal, Nitin; Katsanos, Aristeidis H.; Krogias, Christos; Zand, Ramin; Sharma, Vijay K.; Varelas, Panayiotis; Malhotra, Konark; Paciaroni, Maurizio; Sharaf, Aboubakar; Chang, Jason; Kargiotis, Odysseas; et al.
Abstract: Prior studies suggest an association between Vitamin K antagonists (VKA) and cerebral microbleeds (CMBs); less is known about nonvitamin K oral anticoagulants (NOACs). In this observational study we describe CMB profiles in a multicenter cohort of 89 anticoagulation‐related intracerebral hemorrhage (ICH) patients. CMB prevalence was 51% (52% in VKA‐ICH, 48% in NOAC‐ICH). NOAC‐ICH patients had lower median CMB count [2(IQR:1–3) vs. 7(4–11); P < 0.001]; ≥5 CMBs were less prevalent in NOAC‐ICH (4% vs. 31%, P = 0.006). This inverse association between NOAC exposure and high CMB count persisted in multivariable logistic regression models adjusting for potential confounders (OR 0.10, 95%CI: 0.01–0.83; P = 0.034).